1985
DOI: 10.1002/1520-6807(198504)22:2<208::aid-pits2310220215>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and classroom learning

Abstract: This article discusses the role of perceived self-efficacy during classroom learning of cognitive skills. Self-efficacy refers to personal judgments of performance capabilities in a given domain of activity. Students enter classroom activities with various aptitudes and prior experiences, which affect their initial sense of self-efficacy for learning. During task engagement, students may assess self-efficacy by utilizing cues made cognitively salient by educational practices and which convey information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
193
0
24

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 332 publications
(229 citation statements)
references
References 50 publications
12
193
0
24
Order By: Relevance
“…Given the remedial status of our subjects, it is likely that the coping models' statements seemed more credible. Research shows, however, that once children develop skills, ability attributions exert stronger effects on achievement behaviors (Schunk, 1985). Experiment 2 demonstrated that observing several peers rapidly or gradually learning a cognitive skill promoted self-efficacy for learning, training performance, and posttest self-efficacy and skill as well as did observing a single coping model and better than did observing a single mastery model.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Given the remedial status of our subjects, it is likely that the coping models' statements seemed more credible. Research shows, however, that once children develop skills, ability attributions exert stronger effects on achievement behaviors (Schunk, 1985). Experiment 2 demonstrated that observing several peers rapidly or gradually learning a cognitive skill promoted self-efficacy for learning, training performance, and posttest self-efficacy and skill as well as did observing a single coping model and better than did observing a single mastery model.…”
Section: Discussionmentioning
confidence: 95%
“…Although the videotape teachers did not explicitly instruct the peer models to use these techniques, it is possible that subjects learned that increased concentration and hard work could produce better results. Such beliefs can raise selfefficacy (Bandura, 1986 ;Schunk, 1985). Future researchers might disentangle the effects of increased perceived similarity from those due to modeling of coping techniques by including a treatment in which a peer model uses coping techniques but demonstrates the rapid learning characteristic of a mastery model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asking students to set proximal goals enhanced self-efficacy and skill development more effectively than asking them to set distal goals because the proximal attainments provide evidence of growing capability (Bandura & Schunk, 1981). Verbally encouraging students to set their own goals improved not only their efficacy beliefs and achievement but also their commitment to attaining the goals (Schunk, 1985). The frequency and immediacy of enactive feedback also created higher perceptions of personal efficacy (Schunk, 1983).…”
Section: Instructional and Social Influences On Self-efficacy Beliefsmentioning
confidence: 99%